OD DEMOKRACJI PRZEDSTAWICIELSKIEJ DO DEMOKRACJI PRAWNICZEJ: KONSTYTUCJA STANÓW ZJEDNOCZONYCH A EWOLUCJA USTROJOWA PAŃSTWA - Lewicki, Zbigniew (Zeszyty Prawnicze, 2016)
FROM REPRESENTATIVE DEMOCRACY TO JUDICIAL DEMOCRACY: THE CONSTITUTION OF THE UNITED STATES AND THE EVOLUTION OF THE POLITICAL SYSTEM Summary The article discusses the process in which the judiciary branch has claimed and maintains its supremacy over the other two branches by practicing the extra-constitutional process of judicial review. Prior precedences under the British or colonial rule can hardly be claimed as they were established in a markedly different system in which the tripartite division of power was not as pronounced as it is under the U.S. Constitution. The real culprit is the U.S. Congress which refrains from making clear rules in controversial matters, such as abortion. The Supreme Court swiftly moved into the void to the point where the beliefs of nine nominated Justices outweigh the views of over five hundred elected representatives of the people, to wit: the flag burning controversy. While the learned opinions of nine learned and respected specialists should not be dismissed lightly, it is a far cry from the Founding Fathers’ intention if one person’s preferences can sway the nation’s political system, as is the case when the Court is divided between four liberals and four conservatives. However, lawyers are unlikely to give up the power they have usurped over time.